The effect of video exercise-based telerehabilitation on clinical outcomes, expectation, satisfaction, and motivation in patients with chronic low back pain - SARI, ZÜBEYİR (SPRINGER LONDON LTD, 2022)
Background The efficacy of exercise-based telerehabilitation in chronic low back pain (CLBP) has not been well studied. To our knowledge, no other studies have investigated the efficacy of video exercise-based telerehabilitation software in the remote management of home exercises in patients with CLBP. Aims The purpose of the study was to investigate the effect of the video-based exercise software on pain, function, quality-of-life, expectation, satisfaction, and motivation in individuals with CLBP. Methods A double-blind, two-armed randomized controlled trial was carried out with 50 individuals with CLBP. Participants were randomly allocated to either the telerehabilitation group (n = 25) or the conventional rehabilitation group (n = 25). The telerehabilitation group was followed up with a video exercise-based telerehabilitation software called Fizyoweb. The clinician was able to communicate with the patients through the software. The conventional rehabilitation group was given the same home exercises as the paper-based exercise instruction form. Pain, function, quality-of-life, and kinesiophobia were evaluated at baseline and after 8 weeks of intervention. In addition, patient expectations were questioned at the initial evaluation; afterward, patient satisfaction and motivation were questioned at the eighth week. Results After 8 weeks of treatment, the telerehabilitation group achieved significant improvement in pain, function, quality-of-life, kinesiophobia, satisfaction, and motivation (p < 0.05). In addition, the telerehabilitation group reported more significant gains in all parameters compared with the conventional rehabilitation group (p < 0.05). Conclusions The video exercise-based telerehabilitation software positively affects clinical parameters and adherence to rehabilitation in patients with CLBP.
Keywords: Exercise video; Low back pain; Remote rehabilitation; Telehealth; Telemedicine; MANAGEMENT; REHABILITATION; DISABILITY; THERAPY; PROGRAM